1995
DOI: 10.1063/1.113576
|View full text |Cite
|
Sign up to set email alerts
|

Electron effective masses in 4H SiC

Abstract: Results from optically detected cyclotron resonance (ODCR) studies of electron effective masses in 4H SiC are reported. ODCR measurements were performed on high-purity n-type 4H SiC epitaxial layers grown by chemical vapor deposition at both X band (9.23 GHz) and Q band (35.05 GHz) microwave frequencies. Electron effective masses in 4H SiC were directly determined as m⊥*=0.42m0 and m∥*=0.29m0. A scattering time in the basal plane τ⊥≊4.3×10−11 s, and hence, the corresponding electron mobility μ⊥≊1.8×105 cm2/V s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
33
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(40 citation statements)
references
References 5 publications
7
33
0
Order By: Relevance
“…9, and (b) these results almost perfectly reproduce those of Ref. 40. The significance of these points stems from the fact that they clearly indicate that corrections expected from the application of the BZW procedure are negligible for metallic Ru0 2 * unlike in the case of semiconductors.…”
Section: Electronic Properties and Optical Transitions Of Diamondsupporting
confidence: 77%
See 2 more Smart Citations
“…9, and (b) these results almost perfectly reproduce those of Ref. 40. The significance of these points stems from the fact that they clearly indicate that corrections expected from the application of the BZW procedure are negligible for metallic Ru0 2 * unlike in the case of semiconductors.…”
Section: Electronic Properties and Optical Transitions Of Diamondsupporting
confidence: 77%
“…Consequently, our calculated total density of states (DOS) in Fig. 10 are the same as those of Glassford and Chelikowsky 40 -in qualitative and quantitative terms. These authors did not provide the partial density of states (PDOS) we show in Fig.…”
Section: Electronic Properties and Optical Transitions Of Diamondsupporting
confidence: 58%
See 1 more Smart Citation
“…Son et al 5 also reported an ODCR signal using a higher microwave frequency in the Q-band (ν = 35 GHz). With the correspondingly higher ωτ = 9.1 value, our calculations predict that the mass anisotropy in the c-plane should be clearly resolved for 4H, as can be seen in Fig.…”
mentioning
confidence: 98%
“…Rather conflicting results have been reported on the effective masses as determined by a fitting of IR absorption spectra of the excited shallow donor states 3,4 and by optically detected cyclotron resonance (ODCR). 5,6 In this letter, calculated band structures of 6H SiC and 4H SiC are used to determine the effective mass tensors at the conduction-band minimum. Our results are in good agreement with the ODCR results on the anisotropies with respect to the c-axis for 6H and 4H SiC masses and hence support a mass-anisotropy as the cause for the mobility anisotropies.…”
mentioning
confidence: 99%